PEDAGOGICAL MANAGEMENT OF CREATION OF CONDITIONS, WAYS AND APPROACHES TO THE PERSONALITY OF A STUDENT OF PHYSICS - V.K. Buryak; Yu.V. Reva; A.V. Vernyhora; L.A. Kovalchuk (Academy of Cognitive and Natural Sciences, 2003)
This article deals with the pedagogical government in making conditions, approaches and ways to an individual of a pupil on materials of studying physics.